STUDY OF MARKERS OF BLOOD LYMPHOCYTES APOPTOSIS IN ANIMALS AT HELMINTHIASES - E. A. Grishina (Российский паразитологический журнал, 2019)
Studying the role of apoptosis of blood cells allows to determine more precisely the mechanisms of immunopathology in general, and immunosuppression - in particular. The aim of that research was to study morphological and molecular indicators of apoptosis of peripheral blood lymphocytes in mice infected with Trichocephalus muris and rabbits infected with Passalurus ambiguus to determine possible mechanisms of secondary immunosuppression development under chronisation of helminthiasis. Materials and methods. During the experiment, the animals were divided into the following groups: 1) intact mice (control group) - 15 ind.; 2) intact rabbits (control group) - 10 ind.; 3) mice infected with Trichocephalus muris (Schrank, 1788) - 60 ind.; 4) rabbits infected with Passalurus ambiguous (Rudolphi, 1819 ) - 30 ind. Blood from the tail vein of mice, and the ear vein of rabbits was used to prepare smears 1, 2, 3, 6, 7, 8 weeks after infestation. Light microscopy of blood smears stained by Romanovsky’s method [2] was applied for leucogram determination and investigation of morphological indicators of apoptosis. For molecular studies, mononuclear leukocytes were isolated from venous whole blood by density gradient centrifugation using Ficoll-Paque media (= 1,077 g / cm3, «Pharmacia», Sweden) [12]. The concentration of the pro-apoptotic protein caspase-3 and anti-apoptotic protein Bcl-2 was determined in lysates of lymphocytes by ELISA using kits Human Caspase-3 instant ELISA and the Human Bcl-2 ELISA of the company «Bender MedSystems GmbH» (Vienna, Austria). Results and discussion. The analysis of obtained data shows that at helminth infection of animals and under chronisation of helminthiasis, statistically significant changes occur within 8 weeks in the total number of leukocytes, the total number of lymphocytes and lymphocytes with morphological signs of apoptosis, as well as in pro-apoptotic protein caspase-3 and anti-apoptotic Bcl-2 protein. This comprehensive study convincingly shown that a gradual and significant increase in apoptotic activity of lymphocytes on the receptor and cellular levels is observed in animals in the period from the beginning of infestation up to the chronic stage of helminthiasis. This is manifested in the increased number of lymphocytes with morphological features of apoptosis against the background of the increased level of pro-apoptotic protein caspase-3, and the reduced level of anti-apoptotic protein Bcl-2.